Article 297 of the United Nations Convention on the Law of the Sea and the Scope of Mandatory Jurisdiction. (2nd October 2017) - Allen, Stephen
ABSTRACT: This article assesses the scope and content of the automatic exceptions contained in Article 297 of the UN Convention on the Law of the Sea to the compulsory procedures established in Section 2 of Part XV. The Convention's drafting history is examined with a view to determining the validity of the diametrically opposed readings of Article 297(1) endorsed by Annex VII Tribunals in the Southern Bluefin Tuna Award and the Chagos Marine Protected Area (MPA) Award. The interpretation favoured in the Chagos MPA Award—that mandatory jurisdiction is not restricted to the three cases expressly enumerated in Article 297(1)—is consistent with the textual evolution of Part XV. The article situates the approach adopted by the Chagos Tribunal within a wider normative tradition, which holds that adjudicative jurisdiction arises in default of positive textual authorzsation (unless it has been explicitly excluded). It is argued that this approach should be embraced by courts and tribunals when interpreting the Convention's provisions, as it accords with the drafters' aspirations and it serves to strengthen the international Rule of Law.